Ecological momentary assessment: a meta-analysis on designs, samples, and compliance across research fields - Wrzus, Cornelia; Neubauer, Andreas B. (Assessment, 2022)
Ecological Momentary Assessments (i.e., EMA, repeated assessments in daily life) are widespread in many fields of psychology and related disciplines. Yet, little knowledge exists on how differences in study designs and samples predict study compliance and dropout—two central parameters of data quality in (micro-)longitudinal research.